1996
DOI: 10.1111/j.1468-2958.1996.tb00391.x
|View full text |Cite
|
Sign up to set email alerts
|

Ambiguity and Communication Effects on Small Group Decision-Making Performance

Abstract: The literature that has characterized thejield ofgroup studies has ken conhDversia1 and confusing w'th regard to the effect of communicative and nonwmmunicative variables on p u p decision making. The mazrch reported here &further understanding ofthe mmunicatin-pnfannre relationshy. It is postulated that two claws ofuarinbles (homogeneity and task) moderate the relationship between p u p communication and group pe@munce. This is bemuse the variables contribute to the overall ambiguityfiund in the decision-maki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 76 publications
(78 reference statements)
0
8
0
Order By: Relevance
“…Second, our findings speak to the idea that team role differentiation primarily occurs through interaction among team members (Hare, 1994;Salazar, 1996). Our results suggest the informal structure and role differentiation created in these teams were based on team member interaction.…”
Section: Discussionmentioning
confidence: 49%
“…Second, our findings speak to the idea that team role differentiation primarily occurs through interaction among team members (Hare, 1994;Salazar, 1996). Our results suggest the informal structure and role differentiation created in these teams were based on team member interaction.…”
Section: Discussionmentioning
confidence: 49%
“…Further information related to this skill can be found in Day and Silverman (1989), Hackman (1998), Jacobs and Washington (2003), Mankin (2001), Salazar (1996), and Sundstrom (1998).…”
Section: Preparation (31%)mentioning
confidence: 95%
“…Further information related to this skill can be found in Barrick and Mount (1991), Bedeian and Breeze (1998), Hirokawa (1990), Park andKwon (2004), andSalazar (1996).…”
Section: Sufficiency Of Information (34%)mentioning
confidence: 96%
“…Communication encompasses the verbal messages team members use to share information with each other, but also involves nonverbal factors (such as "body language" and seeming enthusiastic or skeptical), and the relations formed between members as they interact. Several studies have found that the way team members communicate with each other is crucial in determining how they collaborate and the success of those efforts [38][39][40] . However, the precise role of communication in contributing to a group's success is still a matter of debate 41 , with calls for more extensive work analyzing these effects 4 .…”
Section: Team Network Structure and Ethical Interactionsmentioning
confidence: 99%